Influences of alkali incorporation and electrodeposited metal layer on formation of MoS2 in CZTS thin films. (1st November 2021) - Wang, Jiao; Wang, Yanping; Li, Haoran; Zhao, Aimei; Li, Bing; Bi, Jinlian; Li, Wei
Abstract: In this work, the CZTS absorbers were prepared by sol-gel method and the combination of electrodeposition and sol-gel method. The influence of Na and/or K incorporation on the thickness of MoS2 during sulfurization process was investigated. XRD, Raman, and SEM characterizes presented that K incorporation could help to suppress the formation of MoS2, which induced to reduce the thickness of MoS2 . Additionally, Na and/or K doping could eliminate the existence of the voids and improve the quality of CZTS thin film. Besides, the CZTS absorbers fabricated by the combination process of electrodeposition and sol-gel shown a better adhesion than that fabricated by sol-gel method.